Hubungan Kebiasaan Mengunyah Satu Sisi Rahang dengan Kalkulus Indeks pada Mahasiswa Tingkat 1 Jurusan Gizi di Poltekkes Kemenkes Banjarmasin - Amini, Syarifah; Kisworo Utami , Naning; Amperawati, Metty; Ulfah, Rasuna (JURNAL TERAPIS GIGI DAN MULUT, 2024)
Based on preliminary studies by researchers to students of the Nutrition Department of the Poltekkes Kemenkes Banjarmasin by taking 10 respondents. It was obtained from the 10 respondents that 7 respondents chewed with one side of the jaw, while 3 respondents chewed with two sides of the jaw. The purpose of this study was to know the relationship between the habit of chewing one side of the jaw with calculus index in 1st year students majoring in nutrition at the Poltekkes Kemenkes Banjarmasin. This research method uses analytical survey research, the research design uses cross sectional and the sample uses purposive sample with a total sample of 74 person. The results of data analysis using the Chi Square test. The results of this study showed that the majority of respondents had the habit of chewing on one side of their jaw, and the calculus index among first-year nutrition department students was mostly categorized as moderate. The statistical analysis indicated a significant relationship between the habit of chewing on one side of the jaw and the calculus index, with a p-value of 0.000 (p<a, 0.05), indicating the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). In conclusion, there is a relationship between the habit of chewing on one side of the jaw and the calculus index among first-year nutrition department students at Poltekkes Kemenkes Banjarmasin. It is recommended for students to will develop the habit of chewing food using both sides of their jaw.